The guarantee of ne bis in idem and the mitigation of independence among the instances: A study in the light of the new law of administrative improbity in Brazil - Cademartori, Luiz Henrique Urquhart; Hoffmann, Luísa Tramarin; Barbosa, Ronaldo David Viana (Seven Editora, 2023)
This paper discusses the guarantee of ne bis in idem between different sanctioning instances and its contraposition relation with the primacy of independence between the instances, specifically regarding the Brazilian regime of repression of administrative misconduct. It starts with the adoption of the side that defends the incidence of the typical guarantees of the criminal law to the punitive processes ruled by the sanctioning administrative law, from an initial approach of the debate regarding the connections between these two legal branches. Given this discussion, the analysis focuses on the recent changes promoted by the Federal Law 14.230/2021 to the Administrative Misconduct Law (Federal Law 8.429/1992). In this sense, based on a bibliographical review and legislative analysis, it is intended to understand whether the changes promoted in the Administrative Misconduct Law brought new manifestations of the guarantee of ne bis in idem between different sanctioning spheres in the Brazilian legal system, in order to mitigate the traditional independence between the punitive instances enshrined in article 37,  § 4, of the Federal Constitution of 1988. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-041